2007
DOI: 10.4081/ijas.2007.395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oilseed supplements on milk production and quality in dairy cows fed a hay-based diet

Abstract: The influence of rapeseed (Brassica napus L.) and linseed (Linum usitatissimum L.) on feed consumption, milk yield, composition and fatty acid (FA) profile was investigated in lactating dairy cows. According to a Latin square design, twelve cows were assigned to three experimental settings which received a haybased diet supplemented with one of the following mixtures: cracked barley (1.0 kg) and cracked maize (0.5 kg) as Control diet (C-diet); full fat ground rapeseed (1.0 kg), cracked barley (1.0 kg) and crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
5
21
1
Order By: Relevance
“…In contrast to linseed, rapeseed supplementation only increased concentrations of MUFA, OA (the dominant FA found in rapeseed oil), VA and RA, but did not affect the total and individual n-3, thus being in line with previously reported results (Glasser et al, 2008), although some studies report no effect of rapeseed feeding on milk VA and RA concentrations (Collomb et al, 2004;Egger et al, 2007). Differences in the impact of linseed and rapeseed supplementation on milk FA profiles were expected, since: (a) the dominant FA differ -ALA in linseed as opposed to OA in rapeseed (Glasser et al, 2008) and (b) higher ALA intakes result in more ALA escaping RBH and being secreted into milk (Collomb et al, 2004;Egger et al, 2007).…”
Section: Conventional (C1)supporting
confidence: 77%
“…In contrast to linseed, rapeseed supplementation only increased concentrations of MUFA, OA (the dominant FA found in rapeseed oil), VA and RA, but did not affect the total and individual n-3, thus being in line with previously reported results (Glasser et al, 2008), although some studies report no effect of rapeseed feeding on milk VA and RA concentrations (Collomb et al, 2004;Egger et al, 2007). Differences in the impact of linseed and rapeseed supplementation on milk FA profiles were expected, since: (a) the dominant FA differ -ALA in linseed as opposed to OA in rapeseed (Glasser et al, 2008) and (b) higher ALA intakes result in more ALA escaping RBH and being secreted into milk (Collomb et al, 2004;Egger et al, 2007).…”
Section: Conventional (C1)supporting
confidence: 77%
“…As expected, this level of DMI was slightly lower than data observed in other comparable studies (Abel-Caines et al, 1998;Bailoni et al, 2004) and most likely this was related to the high level of NDF as reported by Egger et al (2007). The NDF intake was not affected and averaged 1.06% of BW; this finding was lower than the value reported by Rayburn and Fox (1993) and the level of intake (1.1-1.2 NDF Intake %BW) indicated by Mertens (1987).…”
Section: Feed Intake Productive Performance and Metabolic Profilecontrasting
confidence: 55%
“…Vaccenic increased 6.2-and 4.5-fold (P<0.001); its concentration in milk depended both on its level in the gut and on its conversion in CLA in the udder (Corl et al, 2001;Antongiovanni et al, 2003). In this study, the percentage of CLA in milk was quite low for both diets ( Table 7) when compared with other studies (0.7-1.3%) (Kay et al, 2005;Pottier et al, 2006;Egger et al, 2007). This was probably due to the high level of dietary fibre which leads to a high ruminal pH which, as suggested by Piperova et al (2002), is related to a lower production of BH intermediate compounds; this means a low vaccenic acid supply at duodenal level.…”
Section: Milk Fatty Acid Profilementioning
confidence: 42%
See 1 more Smart Citation
“…In dairy cows, the source of roughage affects the organoleptic and nutritional quality of milk, particularly the fatty acid (FA) profile (Shingfield et al 2005;Egger et al 2007). Differences between grass hay (GH) and maize silage (MS) are evident in single FA contents.…”
Section: Introductionmentioning
confidence: 99%